Proton polarization in reaction of deuteron photodisintegration at energies of 0.2-2.4 GeV - Konovalov, O.G.; Lukyanenko, S.T.; Sorokin, P.V.; Zybalov, A.A. (Вопросы атомной науки и техники, 2002)
The review of the proton polarization experimental data on two-body deuteron photodisintegration at a photon energy between 0.2 and 2.4 GeV is presented. The NSC KIPT data are compared with the measurements of other centers and with theoretical calculations and phenomenological analysis in the framework of various interaction models with subnuclear (nucleons, mesons, resonances) and non-nucleon (quarks, gluons) degrees of freedom. The NSC KIPT measurements are in full accord with the data of other centers up to 0.8 GeV and confirm the dominant contribution of meson-exchange interactions and isobar configurations in the reaction γD→pn. Above 1 GeV the NSC KIPT data do not agree with the Jefferson Lab (USA) measurements which confirm the quark-gluon hypotheses about zero values of the proton polarization in this region.